Analysis The Deed of Sale and Purchase Shares Pretends and Its Consequences on The Strength of The Deed - Raissa Anjani; Sri Laksmi Anindita (LEGAL BRIEF, 2022)
In carrying out the sale and purchase of shares, Notary should ensure that the procedure for the transfer of shares is carried out in accordance with the law, because it can result the validity of the deed made by Notary. As happened in the case in Court Decision No. 1681 K/Pdt/2017, the Judges decided that the Deed of Sale and Purchase made by Notary was a fake deed. In this case, Notary also does not ask for proof of payment of the purchase of shares, so it is said that Notary does not apply the precautionary principle. What can make a Deed of Sale and Purchase as a fake Share Purchase Deed and what are the consequences fot the legal force of the deed are two problem formulations to be analyzed based on juridical research methods and qualitative analysis. From the results of the study, it was found that several factors caused a Deed of Sale and Purchase of Shares to be declared as a fake deed which then affected the legal force of the deed.